Anti-Semitism and Islamophobia: Religio-Political Fault Lines in Secular Democracies - Hedges, Paul (2016)
Seemingly politically inspired and media-led Islamophobic allegations and accusations of anti-semitism marred the recent UK mayoral and local elections. This potentially sets a dangerous precedence for using religious allegations as political tools and must be checked. The implications are applicable to all secular democracies, not just UK.